Factors Associated With High Sodium Intake Based on Estimated 24-Hour Urinary Sodium Excretion: The 2009–2011 Korea National Health and Nutrition Examination Survey. Issue 9 (March 2016) - Hong, Jae Won; Noh, Jung Hyun; Kim, Dong-Jun
Abstract : Abstract: Although reducing dietary salt consumption is the most cost-effective strategy for preventing progression of cardiovascular and renal disease, policy-based approaches to monitor sodium intake accurately and the understanding factors associated with excessive sodium intake for the improvement of public health are lacking. We investigated factors associated with high sodium intake based on the estimated 24-hour urinary sodium excretion, using data from the 2009 to 2011 Korea National Health and Nutrition Examination Survey (KNHANES). Among 21, 199 adults (≥19 years of age) who participated in the 2009 to 2011 KNHANES, 18, 000 participants (weighted n = 33, 969, 783) who completed urinary sodium and creatinine evaluations were analyzed in this study. The 24-hour urinary sodium excretion was estimated using Tanaka equation. The mean estimated 24-hour urinary sodium excretion level was 4349 (4286–4413) mg per day. Only 18.5% (weighted n = 6, 298, 481/3, 396, 973, unweighted n = 2898/18, 000) of the study participants consumed less the 2000 mg sodium per day. Female gender ( P < 0.001), older age ( P < 0.001), total energy intake ≥50 percentile ( P < 0.005), and obesity ( P < 0.001) were associated with high sodium intake, even after adjusting for potential confounders. Senior high school/college graduation in education and managers/professionals in occupation were associated with lower sodium intake ( P < 0.001). According to hypertension management status, those who had hypertension without medication consumed more sodium than those who were normotensive. However, those who receiving treatment for hypertension consumed less sodium than those who were normotensive ( P < 0.001). The number of family members, household income, and alcohol drinking did not affect 24-hour urinary sodium excretion. The logistic regression analysis for the highest estimated 24-hour urinary sodium excretion quartile (>6033 mg/day) using the abovementioned variables as covariates yielded identical results. Our data suggest that age, sex, education level, occupation, total energy intake, obesity, and hypertension management status are associated with excessive sodium intake in Korean adults using nationally representative data. Factors associated with high sodium intake should be considered in policy-based interventions to reduce dietary salt consumption and prevent cardiovascular disease as a public health target.